Immunodeficiency in cartilage‐hair hypoplasia: Pathogenesis, clinical course and management. (22nd June 2020) - Vakkilainen, Svetlana; Taskinen, Mervi; Mäkitie, Outi
Abstract: Cartilage‐hair hypoplasia (CHH) is an autosomal recessive syndromic immunodeficiency with skeletal dysplasia, short stature, hypotrichosis, variable degree of immune dysfunction and increased incidence of anaemia, Hirschsprung disease and malignancy. CHH is caused by variants in the RMRP gene, encoding the untranslated RNA molecule of the mitochondrial RNA‐processing endoribonuclease, which participates in for example cell cycle regulation and telomere maintenance. Recent studies have expanded our understanding of the complex pathogenesis of CHH. Immune dysfunction has a major impact on clinical course and prognosis. Clinical features of immune dysfunction are highly variable, progressive and include infections, lung disease, immune dysregulation and malignancy. Mortality is increased compared with the general population, due to infections, malignancy and pulmonary disease. Several risk factors for early mortality have been reported in the Finnish CHH cohort and can be used to guide management. Newborn screening for severe combined immunodeficiency can possibly be of prognostic value in CHH. Regular follow‐up by a multidisciplinary team should be implemented to address immune dysfunction in all patients with CHH, also in asymptomatic cases. Haematopoietic stem cell transplantation can cure immune dysfunction, but its benefits in mildly symptomatic patients with CHH remain debatable. Further research is needed to understand the mechanisms behind the variability of clinical features, to search for potential molecular treatment targets, to examine and validate risk factors for early mortality outside the Finnish CHH cohort and to develop management guidelines. This review focuses on the pathogenesis, clinical course and management of CHH.